PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN, BUDAYA ORGANISASI DAN LOCUS OF CONTROL TERHADAP KINERJA MANAJERIAL PADA SKPD KABUPATEN MERAUKE - Okto Irianto (Universitas Musamus,Merauke,Papua, 2014)
The purpose of this study was to determine (1) the effect of budget participation on performance of the SKPD in the Merauke district government, (2) the influence of organizational culture on performance of the SKPD in the Merauke district government, (3) the influence of locus of control on performance of the SKPD in the Merauke district government and (4) the simultaneous effect of budget participation, culture and locus of control on the performance of the SKPD in the Merauke district governmentThe sample was SKPD in the Merauke district government. The main instrument for data collection was a questionnaire and measured with a Likert scale. Respondents totaled 67 people. The entire questionnaire filled and managed using multiple regression data analysis.The results showed that the partial budget participation, organizational culture and locus of control positive and significant impact on the performance of the SKPD in the Merauke district government. Meanwhile, simultaneously budgetary participation, organizational culture and locus of control are also positive and significant effect.